Blood Flow and Anatomical MRI in a Mouse Model of Retinitis Pigmentosa - Muir, Eric R (2012)
This study tested the sensitivity of an arterial spin labeling MRI method to image changes in retinal and choroidal blood flow (BF) and anatomical thickness of the retina in the rd10 mouse model of retinitis pigmentosa. High-resolution (42×42μm) MRI was performed on rd10 mice and age-matched controls at 25, 35, and 60 days of age (n=6 each group) on a 7-Tesla scanner. Anatomical MRI was acquired and quantitative BF was imaged using arterial spin labeling MRI with a separate cardiac labeling coil. Histology was obtained to confirm thickness changes in the retina. In control mice, the retinal and choroidal vascular layers were quantitatively resolved. In rd10 mice, retinal BF decreased progressively over time while choroidal BF was unchanged. The rd10 retina became progressively thinner at later time points compared to age-matched controls by anatomical MRI and histology (p<0.01). BF and anatomical MRI were capable of detecting decreased BF and thickness in the rd10 mouse retina. Because BF is tightly coupled to metabolic function, BF MRI has the potential to non-invasively assess retinal diseases in which metabolism and function are perturbed and to evaluate novel treatments, complementing existing retinal imaging techniques.